Manufacturing process and material selection using modified multi criteria decision making for brake disc - Fatchurrohman, Nanang (2013)
In today’s overwhelming competition, the knowledge on product development represents a very significant aspect for companies to survive in the market. Among these sectors is the automotive industry, where it is one of the most fast growing, highly demanding and stiff competition marketplaces. Intensive research in this field is targeted to produce light weight and high performance components which can increase fuel efficiency and sustainability of an automobile. One of the recent avenues is the investigation of increased performance engineered materials to replace the conventional materials. In this study product development of engineered material - metal matrix composites (MMCs) component is explored. To achieve a sound product development,new integrated product development framework which utilised simultaneous approach is developed. The framework is referred to as Integrated Conceptual Selection (ICS) which streamlines the phases in the product development process, including product investigation, product specification and conceptual design. Consequently, in this study a new decision making tool for concept selection process which employed concurrent strategy and combination of techniques i.e. analytical network process (ANP), quality function deployment (QFD) and analytical hierarchy process (AHP) is developed and referred as “CoNQA” technique. By using this new framework and tool, a development of an automotive product - MMCs brake disc is performed. The investigation includes the conceptual selections for the best manufacturing process and material for MMCs brake disc rotor. The conceptual selection of manufacturing process involved 14 criteria and 8 alternatives; meanwhile, the material selection incorporated 14 criteria and 21alternatives. Permanent mould casting was chosen as the best decision for manufacturing process with priority vector of 0.1431. The next alternatives were plaster mould casting and centrifugal casting with priority vectors of 0.1318 and 0.1240 respectively. Furthermore, within the material selection process, MMCs 2124Al alloy-SiCp (10%) was preferred as the best material with priority vector of 0.53629. The next choices were 2124Al alloy-SiCp (15%) and 2124Al alloy-SiCp (20%) with priority vectors of 0.53166 and 0.53050 respectively. The conceptual selections were verified using sensitivity analysis during the selection process. At the final stage of this study, a validation work for the conceptual design study is presented. The validation method is proposed based on sustainable product performance analysis, where it performed parameter analysis and compared between the MMCs and conventional cast iron brake disc. The validation results confirmed that the MMCs brake disc have the potential to outweigh the conventional iron brake disc in terms of sustainability and performance. Hence it validated the proposed concept of MMCs brake disc to be further developed into the next design level aiming for prototyping.